PHB3 regulates lateral root primordia formation via NO-mediated degradation of AUXIN/INDOLE-3-ACETIC ACID proteins. (18th March 2022) - Li, Shuna; Li, Qingqing; Tian, Xiao; Mu, Lijun; Ji, Meiling; Wang, Xiaoping; Li, Na; Liu, Fei; Shu, Jing; Crawford, Nigel M; Wang, Yong
Abstract : PHB3 regulates degradation of IAA28 and IAA14 by controlling nitric oxide accumulation, thereby regulating lateral root founder cell identification and asymmetric division. Abstract: We have previously shown that Arabidopsis thaliana Prohibitin 3 (PHB3) controls auxin-stimulated lateral root (LR) formation; however, the underlying molecular mechanism is unknown. Here, we demonstrate that PHB3 regulates lateral root (LR) development mainly through influencing lateral root primordia (LRP) initiation, via affecting nitric oxide (NO) accumulation. The reduced LRP in phb3 mutant was largely rescued by treatment with a NO donor. The decreased NO accumulation in phb3 caused a lower expression of GATA TRANSCRIPTION FACTOR 23 ( GATA23 ) and LATERAL ORGAN BOUNDARIES DOMAIN 16 ( LBD16 ) through inhibiting the degradation of INDOLE-3-ACETIC ACID INDUCIBLE 14/28 ( IAA14/28 ). Overexpression of either GATA23 or LBD16 in phb3 mutant background recovered the reduced density of LRP. These results indicate that PHB3 regulates LRP initiation via NO-mediated auxin signalling, by modulating the degradation of IAA14/28.